2018
DOI: 10.3775/jie.97.180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preloaded Ferrocene in Co-pyrolysis of Kerosene/Ferrocene on CNT Synthesis

Abstract: Based on elemental analyses, slop oil which is typical petroleum waste could be represented by kerosene according to the major content of hydrocarbons containing 8-15 of carbon atoms. It was found that co-pyrolysis of mixture of kerosene and ferrocene with a certain amount of ferrocene preloaded into a quartz tube reactor could result in formation of carbon nanotubes with uniform morphology and substantial yield. Based on thermogravimetric and SEM analyses, it was found that typical sample of CNTs synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…From Thonganantakul et al [46], CNT yields decreased from 56.0% to 41.1% and 25.7% when molar ratio of kerosene to ferrocene increased from 1:1 to 2.2:1 and 3.3:1, respectively, at synthesis temperature of 900 °C. A decrease in product yield was obtained due to the less amount of Fe particles which was not sufficient for selfassembly of CNT at high molar ratio of kerosene to ferrocene.…”
Section: Synthesis Of Carbon Nanotubesmentioning
confidence: 88%
See 4 more Smart Citations
“…From Thonganantakul et al [46], CNT yields decreased from 56.0% to 41.1% and 25.7% when molar ratio of kerosene to ferrocene increased from 1:1 to 2.2:1 and 3.3:1, respectively, at synthesis temperature of 900 °C. A decrease in product yield was obtained due to the less amount of Fe particles which was not sufficient for selfassembly of CNT at high molar ratio of kerosene to ferrocene.…”
Section: Synthesis Of Carbon Nanotubesmentioning
confidence: 88%
“…Their results revealed that an increase in molar ratio of kerosene to ferrocene decreased CNT yields. At high molar ratio of kerosene to ferrocene, the amount of Fe particles was not sufficient for self-assembly of CNTs [46].…”
Section: Yields Of Cnt Productsmentioning
confidence: 98%
See 3 more Smart Citations